Isolation of Potential Probiotic Bacillus spp. from the Intestine of Nile Tilapia to Construct Recombinant Probiotic Expressing CC Chemokine and Its Effectiveness on Innate Immune Responses in Nile Tilapia - Chatsirin Nakharuthai; Surintorn Boonanuntanasarn; Jirawadee Kaewda; Pimpisut Manassila (Animals, 2023)
This study aimed to investigate the potential probiotic Bacillus spp. from the intestine of Nile tilapia in order to construct a recombinant probiotic for the enhancement of the Nile tilapia immune response. One hundred bacterial isolates from the intestine of Nile tilapia were characterized for species identification using the 16s ribosomal RNA (rRNA). Only Bacillus isolates with exhibited antagonistic activity were investigated for their biological functions, which included protease-producing capacity, bile salts and pH tolerance, antibiotic susceptibility, and pathogenicity tests. According to the best results, Bacillus isolate B29, as closely related to B. subtilis, was selected to construct a recombinant probiotic for the delivery of CC chemokine protein (pBESOn-CC). The existence of recombinant probiotics was confirmed by Western blotting before the feeding trial. In addition, the CC chemokine mRNA level was quantified in the intestine of fish fed probiotics after 30 days of feeding. Total immunoglobulin, lysozyme activity, alternative complement 50 activity (ACH50), and phagocytic activity of fish fed either wild-type or recombinant probiotics were significantly increased, indicating that probiotics could stimulate the Nile tilapia immune system through different processes. Interestingly, the dietary supplementation of recombinant probiotics has a stronger immune response enhancement than the wild-type strain.